The vagal rhizopathies - Honey, Christopher R. (Frontiers in Neurology, 2025)
Neurovascular compression of the tenth cranial nerve, the vagus nerve, can cause recognizable and neurosurgically treatable clinical conditions. This chapter will outline the clinical characteristics unique to vagus nerve compression and highlight both the definitive diagnostic protocol and neurosurgical treatment of these conditions. The vagus nerve has motor, sensory and autonomic components. Neurovascular compression of the motor component can cause hemi-laryngopharyngeal spasm (HELPS syndrome). Compression of the sensory component will cause a neurogenic cough called VANCOUVER syndrome – an acronym for Vagus Associated Neurogenic Cough Occurring due to Unilateral Vascular Compression of its Root. Both are caused by direct compression of the root of the tenth cranial nerve at the brainstem by a blood vessel and can be cured by microvascular decompression (MVD). Since the symptoms of choking and cough are common and blood vessels are often abutting the vagus nerve at the brainstem, it is vitally important to understand the definitive diagnostic protocol to avoid operating on false positives. Since the vagus nerve is far more susceptible to dysfunction during surgery than either the trigeminal or facial nerves, it is also important to understand the surgical nuances of this procedure.